Recurrence rate of hirsutism after 3 different antiandrogen therapies - (:unkn) unknown (MOSBY-YEAR BOOK INC, 1999)
Background: Although antiandrogens are frequently and successfully used to treat hirsutism, little attention has been paid to optimal duration of treatment and recurrence rate after cessation of therapy. Objective: Our purpose was to determine the recurrence rate of hirsutism after 3 different antiandrogen therapies. Methods: Eighty-one hirsute women referred to a tertiary hirsutism clinic were assigned to one of three regimens: spironolactone 100 mg/day with an oral contraceptive, cyproterone acetate 50 mg/day on days 1 to 10 with an oral contraceptive, or flutamide 250 mg twice a day. Hirsutism scores according to the Ferriman-Gallwey scoring system and endocrine parameters were evaluated before, during, and 1 year after withdrawal of treatment regimens. Results: Hirsutism scores decreased significantly and similarly in spironolactone, flutamide, and cyproterone acetate treatment groups. However, 1 year after withdrawal of treatment in all antiandrogen therapy groups, hirsutism returned. Conclusion: Antiandrogens are effective in the treatment of hirsutism. However cessation of antiandrogen therapy is followed by recurrence.
Keywords: CYPROTERONE-ACETATE-ESTROGEN; RANDOMIZED CONTROLLED TRIAL; FLUTAMIDE; SPIRONOLACTONE; EFFICACY; METABOLISM; REMISSION